Tehran Water Museum with the Performance-Oriented Approach to Bionic Architecture - Farokhizad, Faeghe; Sabernejad, Jaleh (Journal of History Culture and Art Research, 2017)
Form and function of architecture in nature, is a process that is perceived as instinctive as the development of internal growth and creation. The most basic level of commitment to life that reveals itself in the form of materials. Architecture form and shape to the beat and rhythm of the invisible life, in fact, it is a process which gives the project structure and the structure of the plan. Every living organism is driven by unchangeable force. Trying to become more efficient form and function. In the natural area is very important that "performance" is defined as the process and relationship and "form" is defined as a result of this process. Forms of interaction with nature that takes shape and naturally goes in the direction of performance to match its relationship with the wider environment and in the surrounding territory. Methods and new ideas can be learned from nature. Generally architecture is defined as to imagine, design, understanding and build according to circumstances. These problems may in itself was fully functional and to varying degrees, reflecting the economic, political and social project. In any case, it seems that the status quo is not simply satisfying. For this reason, we seek a new agreement that they "answer the question" is called. Therefore, in this study, based on architectural features permit, trying to establish a performance-oriented architecture, nature-based design and natural patterns to be defined by Vitruvius